Characterization of Phosphofructokinase Activity in Mycobacterium tuberculosis Reveals That a Functional Glycolytic Carbon Flow Is Necessary to Limit the Accumulation of Toxic Metabolic Intermediates under Hypoxia - Phong, W.Y. (2014)
10.1371/journal.pone.0056037